Local and landscape factors differentially influence predatory arthropods in urban agroecosystems - Heidi Liere; Sanya Cowal (Ecosphere, 2024)
Abstract Like other urban green spaces, urban community gardens can act as biodiversity refugees, especially for small organisms like arthropods. In turn, arthropods can provide important ecosystem pest control services to these agroecosystems. Thus, an often‐asked question among urban gardeners is how to improve gardens and surrounding areas for natural enemies and associated pest control services. We examine how local vegetation and garden characteristics, as well as the surrounding landscape composition, affect ground‐dwelling beetles (Coleoptera: Carabidae and Staphylinidae), spiders (Araneae), opilionids (Opiliones), and ladybird beetles (Coleoptera: Coccinellidae), all of which are important predators. In the summer of 2019, we collected predators, vegetation, ground cover, and garden and landscape characteristic data from 10 community gardens in the city of Seattle, Washington. We found that different groups of natural enemies are associated with different environmental variables and at different scales; probably related to differences in their dispersal capabilities, habits, and diets. Floral variables (number of flowers and number of species in flower) had a negative effect on nonflying natural enemies (spiders, opilionids, and ground‐dwelling beetles), but not on flying ones (ladybird beetles). The only taxon that was significantly affected by a landscape‐scale variable was Opiliones, the only group examined that exclusively disperses by ground. Our results show contrasting results to similar studies in different regions and highlight the need to expand the taxa and regions of study.